Policy Transfer In Critical Perspective: The Case Of Malaysia My Second Home Programme - Abdul Rahman, Nurulhasanah (2022)
Malaysia My Second Home Programme (MM2H) was established in 2002 as a government initiative programme to promote Malaysia as a retirement hub for financially qualified foreigners. Although the programme is in high demand to boost Malaysia‟s economy and tourism industry, the actual MM2H programme achievement is hampered by many policy problems. Therefore, it is crucial to investigate the root of the problem by analysing the programme using the policy transfer approach. To address this need, the focus of the study aimed to explore the exact process of policy transfer in the MM2H programme and propose recommendations for policy improvement.